Contemporary challenges in project development: Interventions on works by architect Julio Vilamajó (ARQUISUR Revista, 2015)
"Contemporary Challenges in Project Development" is a reflection paper which discusses issues encountered by architects when intervening on buildings of heritage value, designed by prominent modern architects. The article discusses original buildings highly praised by the architectural culture and the historiography of national architecture. Three relevant works by the Uruguayan architect Julio Vilamajó built between 1931 and 1947 have been selected for the present study. Corresponding to different locations, scales and architectural programs, they had all fallen into partial or total abandonment with the passing of time. The analysis focuses on three contemporary projects aimed at adapting these buildings to new needs and requirements. The essence of the problem lies in discovering and understanding the compositional nature and the spirit of the pre–existing structures, as well as acknowledging their qualities and original values: which of these remain unchanged, which are transformed and what new value an intervention is capable of offering.
Keywords: modern architecture; heritage; building rehabilitation